Transabdominal ultrasonography to reduce the burden of X‐ray imaging in prophylactic pancreatic stent localization after ERCP—A prospective trial. Issue 4 (22nd April 2021) - Michael, Florian Alexander; Gerber, Ludmilla; Weiler, Nina; Hunyady, Peter Marton; Abedin, Nada; de la Vera, Anna‐Lena Laguna; Stoffers, Philipp; Filmann, Natalie; Zeuzem, Stefan; Bojunga, Jörg; Friedrich‐Rust, Mireen; Dultz, Georg
Abstract: Background: Before performing endoscopy to remove prophylactic pancreatic stents placed in patients with high risk of post‐endoscopic retrograde cholangiopancreatography pancreatitis (PEP), X‐ray imaging is recommended to confirm the stents position in the pancreatic duct. Objectives: The aim of the present study was to investigate the feasibility of prophylactic pancreatic stent detection by transabdominal ultrasonography, to reduce the burden of X‐ray imaging, which is currently the golden standard. Methods: All patients who received a pancreatic stent for PEP prophylaxis were included in the present prospective trial. First, stent position was determined by transabdominal ultrasonography. Afterwards, it was verified by X‐ray imaging. Retained stents were removed by esophagogastroduodenoscopy. Dislocated stents needed no further intervention. Results: Fourty‐one patients were enrolled in this study. All prophylactic pancreatic stents were straight 6 cm long 5 Fr stents with external flap. All stents were removed between day 1 and 10 (median: 3 days) in all cases. In 34 of 41 cases (83.0%), the pancreatic stent was still in place on the day of examination. Twenty‐nine of 34 (85.3%) stents were detected correctly by transabdominal ultrasonography. Overlying gas prevented visualization of the pancreas in 3/41 (7.3%) cases. Sensitivity of sonographic detection of the stent was 93.5% (29/31). Six of seven stents were determined correctly as dislocated by ultrasonography. Here, specificity was 85.7%. A positive predictive value of 96.7% (29/30) was examined. The negative predictive value was 75.0% (6/8). Conclusion: Transabdominal ultrasonography detects the majority of prophylactic pancreatic stents. Thereby, it helps to identify patients with an indication for endoscopy sufficiently. X‐ray imaging could subsequently be omitted in about 70% of examinations, reducing the radiation exposure for the patient and the endoscopy staff.